Acute Disseminated Encephalomyelitis in a case of Hyper IgM Syndrome - Devdeep Mukherjee; Ritabrata Kundu; Prabal Niyogi; Joydev Tudu (Journal of Krishna Institute of Medical Sciences University, 2014)
Hyper IgM syndrome is a rare genetically heterogenous syndrome and is characterized by an elevated or normal serum IgM and decreased IgG, IgA and IgE, indicating a defect in the class – switch recombination (CSR) process. Patients are prone to recurrent infections. X linked variety occurring in males is the most common form of the disease. Acute Disseminated Encephalomyelitis (ADEM) in a case of Hyper IgM syndrome has never been reported. Here we report a 10 years old female with hyper IgM syndrome, possibly autosomal form of the disease, who was admitted with recurrent vomiting, seizures, encephalopathy, expressive aphasia and bladder bowel dysfunction and diagnosed to have ADEM.